LAW ENFORCEMENT EDUCATION ON THE CRIMINAL ACTS OF EMBEZZLEMENT IN ONLINE ARISAN IN GARUT REGENCY - Mulyana, Yusep; Ermaya, Berna (MSJ : Majority Science Journal, 2025)
Abstract This research uses a normative juridical method that focuses on the analysis of positive legal norms related to law enforcement against criminal acts of embezzlement in online arisan in Garut Regency. The results of the analysis show that law enforcement conducted by the police consists of two stages, namely preventive efforts through public appeals and socialization, and repressive efforts through investigation, inquiry, examination, and case submission to the Public Prosecutor. Inhibiting factors in law enforcement include limited facilities and infrastructure, limited technological capabilities, operational cost constraints, and low public legal awareness. The results of the analysis show that law enforcement efforts carried out by the police are taken through two stages, namely the prevention stage (preventive) and the enforcement stage (repressive). Prevention (preventive) carried out by the police is two stages starting from appealing to the public through social media and carrying out socialization to the community, then at the stage of law enforcement through enforcement (repressive) carried out by investigators and police investigators through several stages, namely the investigation stage, the investigation stage, the examination stage and the settlement stage and the handover of the case to the Public Prosecutor. The police as the front line strives for the best for the community, all stages of law enforcement are guided by the Criminal Procedure Code (KUHAP) starting from investigations, namely collecting evidence, witnesses, summoning related parties to summoning suspects and making an Examination Report (BAP). Inhibiting factors in Law Enforcement Against the Crime of Embezzlement in Online Arisan in Garut Regency are factors of means and facilities, law enforcement factors, operational cost factors, and community factors to support the investigation process in efforts to examine the disclosure of perpetrators of online arisan embezzlement in the Police's jurisdiction.